Existence and Controllability Results for Impulsive Stochastic Integrodifferential Systems with State-Dependent Delay - Fall, Mbarack; Gnonlonfoun, Abdoule W.; Diop, Mamadou Abdoul; Ogouyandjou, Carlos (Discontinuity, Nonlinearity, and Complexity, 2026)
This work is concerned with the existence and controllability of impulsive stochastic integrodifferential systems with state-dependent delay in a real separable Hilbert space. The main results are obtained by using stochastic analysis theory, fixed point techniques and, Grimmer’s resolvent operator theory. Finally, an example is provided to illustrate the proposed theory.